2023
DOI: 10.21037/tlcr-22-712
|View full text |Cite
|
Sign up to set email alerts
|

Significance of circulating tumor cells in lung cancer: a narrative review

Abstract: Background and Objective: In cancer patients, circulating tumor cells (CTCs) are employed as "Liquid Biopsy" for tumor detection, prognosis and assessment of the response to therapy. CTCs are responsible for tumor dissemination but the mechanisms involved in intravasation, survival in the circulation and extravasation at secondary sites to establish metastases are not fully characterized. In lung cancer patients, CTCs are present in very high numbers in small cell lung cancer (SCLC) that is found disseminated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 173 publications
0
2
0
Order By: Relevance
“…After DNA amplification, it is now possible to directly, qualitatively and quantitatively examine ctDNA using well-established detection techniques such as NGS and digital PCR owing to the rapid improvement of DNA sequencing technology. The therapeutic application value of ctDNA has to be further validated through many pertinent clinical trials and standardize the detection process ( 209 ). EVs have generated much attention in liquid biopsy of cancer as a possible biomarker for cancer detection.…”
Section: Discussionmentioning
confidence: 99%
“…After DNA amplification, it is now possible to directly, qualitatively and quantitatively examine ctDNA using well-established detection techniques such as NGS and digital PCR owing to the rapid improvement of DNA sequencing technology. The therapeutic application value of ctDNA has to be further validated through many pertinent clinical trials and standardize the detection process ( 209 ). EVs have generated much attention in liquid biopsy of cancer as a possible biomarker for cancer detection.…”
Section: Discussionmentioning
confidence: 99%
“…The main cause of death in cancer patients is metastasis. A number of studies have shown that circulating clusters of tumor cells are associated with a greater risk of metastasis and relapse in NSCLC patients than single circulating tumor cells[ 46 - 48 ]. Previously, we proposed a possible mechanism for the formation of tumor cell clusters in tumor MVs[ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, increasing evidence suggests that intravasation of single, apoptotic or clusters of tumor cells can occur via leaky neoangiogenetic vessels in the tumor core and not by crossing the adjacent tumor stroma after EMT[ 48 ]. Hamilton et al [ 48 ] emphasized that some tumor emboli may be located in blind nonfunctioning tumor vessels, which may limit their entry into the bloodstream. We believe that these data indirectly confirm the possibility of the formation of circulating clusters of tumor cells by the mechanism of cavity-type angiogenesis described above.…”
Section: Discussionmentioning
confidence: 99%
“…CTCs can enter the circulation through irregular tumor vessels as single cells or circulating tumor micro-emboli [44]. Certainly, the small cell size (about 8 µm) and high pulmonary blood perfusion are crucial factors for the spread of CTCs [45,46]. It has been shown that although clusters of CTCs are rare in peripheral blood, they have greater metastatic potential than single CTCs [47] and that, in contrast, patients who had no clusters at baseline had significantly better progression-free survival (PFS) (8.2 vs. 4.6 months, p < 0.001) and OS (10.4 vs. 4.3 months, p < 0.001) than patients who had clusters of CTCs at the same time-point [44].…”
Section: Circulating Tumor Cells (Ctcs)mentioning
confidence: 99%